The association between cold hypersensitivity in the hands and feet and chronic disease: results of a multicentre study - Kwang-Ho Bae; Ho-Yeon Go; Ki-Hyun Park; Ilkoo Ahn; Youngheum Yoon; Siwoo Lee (BMC, 2018)
Abstract Background Cold hypersensitivity in the hands and feet (CHHF) is a common symptom in Korea and patients with CHHF complain of coldness in the hands and feet in an environment that is not considered cold by unaffected people. In traditional East Asian medicine, CHHF is believed to be accompanied by various diseases and symptoms, and is considered a symptom that needs active treatment. CHHF is used for pattern identification in the cold pattern, yang deficiency, and constitution. This study aimed to examine the differences in frequencies of chronic diseases with respect to the presence of CHHF. Methods Disease history, CHHF, body measurements, and blood test survey data from 6149 patients collected by 25 medical institutes in Korea were obtained from the Korean Medicine Data Center. The participants were divided into CHHF (n = 1909) and non-CHHF groups (n = 3017) according to the CHHF survey. The differences in frequencies of 18 diseases were analysed using chi-square tests, and the odds ratios (ORs) for each disease according to CHHF status were examined via logistic regression with adjustment for age, sex, and body mass index (BMI). Results Based on chi-square test results, the CHHF group showed a higher frequency of the following diseases: anaemia, hypotension, chronic gastritis, reflux oesophagitis, chronic rhinitis, dysmenorrhoea, and gastroduodenal ulcer. Diseases found in lower frequencies were as follows: hypertension, diabetes mellitus, impaired fasting glucose, dyslipidaemia, stroke, fatty liver, and angina pectoris. In addition, from the logistic regression with adjustment for age, sex, and BMI, the CHHF group showed a lower OR in diabetes mellitus and dyslipidaemia than the non-CHHF group, but a higher OR in degenerative arthritis, chronic gastritis, gastroduodenal ulcer, reflux oesophagitis, and chronic rhinitis. Conclusions This study showed that CHHF is associated with chronic disease. Further large-scale prospective studies are needed to validate these associations.